2022
DOI: 10.1021/acs.inorgchem.1c03931
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Gate-Opening Mechanism in the Flexible Metal–Organic Framework UTSA-300

Abstract: Atomic-level understanding of the gate-opening phenomenon in flexible porous materials is an important step toward learning how to control, design, and engineer them for applications such as the separation of gases from complex mixtures. Here, we report such mechanistic insight through an in-depth study of the pressure-induced gate-opening phenomenon in our earlier reported metal–organic framework (MOF) Zn­(dps)2(SiF6) (dps = 4,4′-dipyridylsulfide), also called UTSA-300, using isotherm and calorimetry measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Consequently, the effective adsorption of Mcy by X-HOF-5a is hindered. On the contrary, while Tol molecules are absorbed on the surface of X-HOF-5a, they can readily diffuse into the crystal through 1D voids because strong intermolecular weak interactions may induce opening of these small holes and subsequently trigger a phase transformation from X-HOF-5a to X-HOF-5. However, due to the sluggish nature of the crystal phase transition, it necessitates several hours for X-HOF-5a to achieve saturation upon adsorbing Tol. Subsequently, X-HOF-5a is anticipated to serve as an efficacious adsorptive separation material for the excellent separation of Tol and Mcy.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Consequently, the effective adsorption of Mcy by X-HOF-5a is hindered. On the contrary, while Tol molecules are absorbed on the surface of X-HOF-5a, they can readily diffuse into the crystal through 1D voids because strong intermolecular weak interactions may induce opening of these small holes and subsequently trigger a phase transformation from X-HOF-5a to X-HOF-5. However, due to the sluggish nature of the crystal phase transition, it necessitates several hours for X-HOF-5a to achieve saturation upon adsorbing Tol. Subsequently, X-HOF-5a is anticipated to serve as an efficacious adsorptive separation material for the excellent separation of Tol and Mcy.…”
Section: Results and Discussionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18] Recently, MOFs have attracted increasing attention for their potential applications in C 2 hydrocarbon separation (C 2 H 2 /C 2 H 4 , C 2 H 4 /C 2 H 6 , and C 2 H 2 /C 2 H 6 , etc.). [19][20][21][22][23][24][25] To improve the separation performance of MOFs, several strategies have been proposed, including pore size customization, pore surface functionalization, open metal sites (OMSs), etc. Since the first porous MOF (M′MOF) for C 2 H 2 /C 2 H 4 separation was reported in 2011, researchers have taken considerable effort to implement some porous MOFs to achieve their efficient separation.…”
Section: Introductionmentioning
confidence: 99%
“…). 19–25 To improve the separation performance of MOFs, several strategies have been proposed, including pore size customization, pore surface functionalization, open metal sites (OMSs), etc. Since the first porous MOF (M′MOF) for C 2 H 2 /C 2 H 4 separation was reported in 2011, researchers have taken considerable effort to implement some porous MOFs to achieve their efficient separation.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging as a new class of porous materials, metal–organic frameworks (MOFs) have witnessed great success in the last two decades toward gas storage, separation, catalysis, etc. Remarkably, reticular chemistry , of MOFs has played important roles in the binary separation of C 2 H 2 /C 2 H 4 and C 2 H 4 /C 2 H 6 by virtue of isoreticular and/or isostructural extension/contraction/expansion/functionalization approaches. Very recently, a few groups have even reported that a single MOF material is capable of simultaneous removal of both C 2 H 2 and C 2 H 6 from a ternary mixture of C 2 H 2 /C 2 H 4 /C 2 H 6 to enable C 2 H 4 purification by a single-step process. Additionally, Zaworotko and Chen et al employed the synergistic sorbent separation technique to pack three task-specific MOFs in a fixed-bed column to empower high-purity C 2 H 4 production from the aforementioned ternary mixture …”
Section: Introductionmentioning
confidence: 99%